Juridical Issues of Copyright on Generative AI Artworks and the Redefinition of Legal Subjects - Meiria Nurphi; Nurheti Nurheti; Ditha Alvira (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2026)
This study analyzes the copyright ownership status of generative AI artworks under Law No. 28 of 2014 on Copyright and the urgency of redefining legal subjects in Indonesia. Using a normative juridical method with statutory and conceptual approaches, this study finds that Indonesia's copyright regime, which adheres to the principle of human authorship, creates a legal vacuum for works autonomously generated by artificial intelligence. This research examines three legal protection scenarios: works as public domain, user ownership, and the concept of computer-aided works. The analysis results indicate that granting independent legal subject status to AI (electronic personhood) is not yet urgent and risks disrupting the doctrine of civil liability. As a solution, the study recommends an approach of attributing rights to humans with dominant creative contributions or the formation of more adaptive sui generis regulations.